Wealth Inequality and Carbon Emissions in High-income Countries. (October 2017) - Knight, Kyle W.; Schor, Juliet B.; Jorgenson, Andrew K.
This study contributes to the emerging literature on connections between climate change and economic inequality by investigating the relationship between domestic wealth inequality and consumption-based carbon emissions for 26 high-income countries from 2000 to 2010. Results of the two-way fixed effects longitudinal models indicate that the effect of wealth inequality, measured as the wealth share of the top decile, on per capita emissions in high-income countries is consistently positive and relatively stable over the time period. This finding is consistent with political economy theories arguing that the concentration of political and economic power that accompanies the concentration of wealth plays an important role in increasing environmental degradation and preventing proenvironmental actions.